2003
DOI: 10.1016/s0378-1097(02)01197-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial leader peptides for protein secretion

Abstract: The leader peptide of the major secreted protein PilA1 of the cyanobacterium Synechocystis sp. strain PCC 6803 and several artificial leader peptides have been used to study secretion of the reporter protein lichenase to the culture medium. The strains of Synechocystis carrying lichenase with the leader sequences of PilA and with the leader sequence of Slr2016 efficiently secreted the reporter protein. The artificial leader sequence that was characterized by the overall positive charge (as PilA1 and Slr2016 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…It was suggested that these proteins were not essential under the steady state growth condition used in the study, although absence of these proteins affected the rate of Chl synthesis and of the assembly of Chl -binding proteins (He and Vermaas 1999). Sll1694 was also identified as a secreted protein that reached the outer surface of the cell (Sergeyenko and Los 2003). The most definitive work to date has involved motility.…”
Section: Differential Gene Expression In Disia Under Normal Growth Comentioning
confidence: 99%
“…It was suggested that these proteins were not essential under the steady state growth condition used in the study, although absence of these proteins affected the rate of Chl synthesis and of the assembly of Chl -binding proteins (He and Vermaas 1999). Sll1694 was also identified as a secreted protein that reached the outer surface of the cell (Sergeyenko and Los 2003). The most definitive work to date has involved motility.…”
Section: Differential Gene Expression In Disia Under Normal Growth Comentioning
confidence: 99%
“…PCC 6803 by biochemical isolation yielded only a low number of hits and contained periplasmic and outer membrane proteins (Sergeyenko and Los, 2000). By analysing individual proteins, it could be demonstrated that PilA1 (Sll1694), PilA10 (Slr2016), HlyA (Sll1951) as well as CccS (Slr1667) and CccP (Slr1668) are secreted to the extracellular space (Sergeyenko and Los, 2003;Sakiyama et al, 2006;Yoshimura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After harvesting, densitometric analysis indicated a Tf AA10A yield of 779 ± 40 µg L −1 in the culture medium without further optimization (Additional file 1: Figure S4). Although the lack of quantification data in other cyanobacterial secretion studies hinders widespread comparisons, to our knowledge, this is the highest yield reported to date for the secretion of a heterologous enzyme in cyanobacteria [24, 25, 63]. Although our reported yield of secreted LPMO is approximately 25% of previously reported yields for E. coli Tf AA10A expression (3 mg L −1 ), the majority of Tf AA10A in E. coli was exported to the periplasm [30], whereas the S. elongatus UTEX 2973 Tf AA10A was fully secreted to the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Although protein export and secretion pathways in cyanobacteria have been studied for almost two decades, they remain poorly understood (see recent reviews [21, 23]). Proof-of-concept studies have shown that heterologous protein secretion in cyanobacteria is possible, however, these studies have generally utilized native signal peptides fused to reporter proteins and have suffered from low yields [24, 25]. In this work, we engineered an industrially relevant extracellular enzyme, a lytic polysaccharide monooxygenase (LPMO), into the fast-growing cyanobacterium S. elongatus UTEX 2973 to assess its secretion capabilities.…”
Section: Introductionmentioning
confidence: 99%